Hyperthermal velocity distributions of recombinatively-desorbing oxygen from Ag(111) - Dorst, Arved C.; Dissanayake, Rasika E. A.; Schauermann, Daniel; Knies, Sofie; Wodtke, Alec M.; Killelea, Daniel R.; Schäfer, Tim (Frontiers in Chemistry, 2023)
This study presents velocity-resolved desorption experiments of recombinatively-desorbing oxygen from Ag (111). We combine molecular beam techniques, ion imaging, and temperature-programmed desorption to obtain translational energy distributions of desorbing O2. Molecular beams of NO2 are used to prepare a p (4 × 4)-O adlayer on the silver crystal. The translational energy distributions of O2 are shifted towards hyperthermal energies indicating desorption from an intermediate activated molecular chemisorption state.